Optimizing VGOS observations using an SNR-based scheduling approach - Matthias Schartner; Bill Petrachenko; Mike Titus; Hana Krásná; John Barrett; Dan Hoak; Dhiman Mondal; Ming Hui Xu; Benedikt Soja (Earth, Planets and Space)
Abstract The geodetic and astrometric very long baseline interferometry (VLBI) community is in the process of upgrading its existing infrastructure with the VLBI Global Observing System (VGOS). The primary objective of VGOS is to substantially boost the number of scans per hour for enhanced parameter estimation. However, the current observing strategy results in fewer scans than anticipated. During 2022, six 24-h VGOS Research and Development (R&D) sessions were conducted to demonstrate a proof-of-concept aimed at addressing this shortcoming. The new observation strategy centers around a signal-to-noise (SNR)-based scheduling approach combined with eliminating existing overhead times in existing VGOS sessions. Two SNR-based scheduling approaches were tested during these sessions: one utilizing inter-/extrapolation of existing S/X source flux density models and another based on a newly derived source flux density catalog at VGOS frequencies. Both approaches proved effective, leading to a 2.3-fold increase in the number of scheduled scans per station and a 2.6-fold increase in the number of observations per station while maintaining a high observation success rate of approximately 90 % to 95 %. Consequently, both strategies succeeded in the main objective of these sessions by successfully increasing the number of scans per hour. The strategies described in this work can be easily applied to operational VGOS observations. Besides outlining and discussing the observation strategy, we further provide insight into the resulting signal-to-noise ratios, and discuss the impact on the precision of the estimated geodetic parameters. Monte Carlo simulations predicted a roughly 50 % increase in geodetic precision compared to operational VGOS sessions. The analysis confirmed that the formal errors in estimated station coordinates were reduced by 40 % to 50 %. In addition, Earth orientation parameters showed significant improvement, with a 40 % to 50 % reduction in formal errors. Graphical Abstract